Support Group Method to Reduce Quarter Life Crisis - Machika Basuki; Djudiyah Djudiyah (Yayasan Adra Karima Hubbi, 2024)
In every phase of development, individuals usually begin to feel uncertainty in facing reality, filled with feelings of doubt and tend to overthink what is happening in their lives. Quarter life crisis is a common phenomenon in individuals in the age range of 20-29 years, which is characterized by anxiety, confusion, and uncertainty about the future. This study aims to explore the effectiveness of the support group method in helping individuals deal with quarter life crisis. This study used a quasi-experimental design with one group pre-test and post-test, involving 5 subjects selected by purposive sampling. The support group intervention was conducted in 3 sessions, with experience sharing activities and assignments to help subjects recognize and overcome their problems. The results showed that there was a significant difference between the pre-test and post-test scores (p=0.043). The support group method is proven to reduce anxiety levels and provide psychological support to individuals experiencing a quarter life crisis.